(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes the pedagogical views of the Muslim Renaissance. The historical truth is that the land of Transoxiana was considered a place of enlightenment and culture in the medieval Muslim East. The scientific heritage of al-Khwarizmi, al-Farghani, al-Farabi, Ibn Sina, Beruni, Zamakhshari and other great scholars and encyclopedists who came from our country has rightfully become a universal property. If in the former Soviet era a one-sided attitude towards the scientific heritage of these scientists was formed, then by the years of independence a comprehensive and in-depth study of the activities and scientific heritage of these great people began.